Vanishing paradise : the tropical rainforest - Dalton, Stephen; Bernard, George, 1949-; Mitchell, Andrew, 1937- (Woodstock, N.Y. : Overlook Press, 1990)
Photographs and text explore life in the South American rainforest.
Includes index.
Booklist.
Adult.
Adult
Keywords: Rain forest ecology; Rain forest ecology -- South America; Rain forests; Rain forests -- South America; Rain forest ecology -- South America; Rain forests -- South America